Evaluasi Keputusan Menteri Dalam Negeri Nomor 17 Tahun 2000 tentang Sistem Informasi Manajemen Kepegawaian (SIMPEG) di Kabupaten Pemalang - Lesmana, Dino Angga; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aims to evaluate of the implementation of the Keputusan Menteri Dalam Negeri Number.17 of 2000 about Human Resources Management Information System which is applied in the Subbidang Dokumentasi dan Pengolahan Data Badan Kepegawaian Daerah Pemalang Regional and describe the factors that support and obstruct the implementation of the policy. This study uses three main aspects, namely the system and the four factors that affect by qualitative descriptive approach. Data collection techniques were used observation, interviews, documentation and literature study with the informant of employees Subbidang Dokumentasi dan Pengolahan Data Badan Kepegawaian Daerah Kabupaten Pemalang. Based on the results of the study, researchers concluded that the results of the evaluation of the implementation of Keputusan Menteri Dalam Negeri Number.17 of 2000 on Human Resources Management Information System applied in the Badan Kepegawaian Daerah Pemalang Regional has been well. This is indicated by the clarity of access, timetables and mechanisms of the program activities and services that systematic implementation of the tasks according to the procedure, successfully serving the SIMPEG data process consideration decision making, evaluation of e-file is routinely conducted, applying the principle of transparency of information and have a proactive attitude in refining the program to successfully develop online SIMPEG, Management Information System performance Analysis and Mapping Management Information Systems Master. It's only that they found several inhibitors that cause results still not maximized, such as the limited number of executive staff, executive staff competence is still not evenly distributed, using the old SOPs and the lack of participation of civil servants to actively evaluate their own data. To overcome these problems, there are some suggestions that can be done such as system development should be supported by education and training as increased capacity and competence of staff implementing evenly, fix the coordination to support the data updating, create SOPs / guidelines contain standards to assess whether it is appropriate with the purpose or not, and disseminate to all civil servants to actively evaluate the data itself through the access rights granted.